Establishment of a cochlear injury model using bone-conducted ultrasound irradiation in guinea pigs and investigation on peripheral coding and recognition of ultrasonic signals - Wang, Fusen; Cao, Cheng; Huang, Chengcheng; Li, Qian; Li, Tiegang; Liu, Xia; Zhang, Shaoyan; Ceng, Xinyu; Wang, Chaoyan (Cellular and Molecular Biology, 2018)
The cochlea of guinea pigs was irradiated with different frequencies of bone-conducted ultrasound (BCU) at a specific dose to induce cochlear hair cell-specific injuries, in order to establish frequency-related cochlear hair cell-specific injury models. Cochlear near-field potentials were then evoked using BCU of different frequencies and intensities to explore the peripheral coding and recognition of BCU by the cochlea. The inner ears of guinea pigs were irradiated by 30 kHz at 100 db and 80 kHz at100 db BCU for 6h to create frequency-related, ultrasound-specific cochlear injury models. Then, 30 kHz and 80 kHz BCU of different intensities were used to evoke auditory brainstem response (ABR) thresholds, compound action potential (CAP) thresholds, and action potential (AP) intensity-amplitude input-output curves in the normal control group and the ultrasonic cochlear injury group. This allowed us to explore the coding and recognition of BCU frequencies and intensities by cochlear hair cells. Immunofluorescence assay of outer hair cell (OHC) Prestin and inner hair cell (IHC) Otofelin was performed to verify the injury models. Irradiation of guinea pig inner ears by 30 kHz and 80 kHz BCU at a specific dose induced hair cell injuries at different sites. Irradiation with low frequency BCU mainly induced OHC injury, whereas irradiation with high frequency BCU induced IHC injury; moreover, IHC injury was more serious than OHC injury. The 30 kHz-evoked ABR threshold was significantly higher in the 30 kHz ultrasonic cochlear injury group compared to the normal control group. The 30 kHz-evoked ABR threshold was significantly higher in the 30 kHz ultrasonic cochlear injury group compared to the 80 kHz ultrasonic cochlear injury group. The difference in the 80 kHz-evoked ABR thresholds were not significant between the 30 kHz and 80 kHz ultrasonic cochlear injury groups. The click- and 30 kHz-evoked AP intensity-amplitude curves for the 30 kHz ultrasonic cochlear injury group indicate that the AP amplitude evoked at the same intensity was higher in the 30 kHz-evoked group than the click-evoked group. The spatial positions of cochlear hair cells in guinea pigs had a coding function for the frequencies of low-frequency ultrasound. OHCs have an amplification effect on the coding of low-frequency ultrasonic intensities. The peripheral perception of high frequency BCU may not require the participation of cochlear hair cells.